Duplication of Nomina in Minangkabau Language in Daily Use in the City of Padang - Darmawan, Alex; Rahmat, Wahyudi (Faculty of Humanities, Andalas University, Padang, West Sumatra in cooperation with Kato Institute., 2022)
In the Minangkabau language of Indonesia, the class of nouns can have multiple forms, which are used frequently in everyday conversation. The Minangkabau language contains examples of both of these types of word reduplication. According to our line of reasoning, reduplication occurs when the Minangkabau language, which is currently in a relatively complex linguistic state, becomes one of the internal states with power in speech when the speaker delivers it. In addition to the functions and meanings that emerge as a direct consequence of these replications, the phenomenon provides very convincing evidence. First, this article describes the various types of reduplication found within the class of nouns in the Minangkabau language. After that, the functions and meanings derived from each type of reduplication will be found. Specifically, the article focuses on the duplication of nouns and discusses the reduplication of adjectives and verbs. To accomplish this goal, the distributional method and various applications of the technique are the approaches that are taken as their respective approaches. As a result of the findings of the analysis, several distinct types of reduplication forms were found to exist within the Minangkabau language. The first category included nothing but nouns that were used repeatedly. The second point is that the affix is present within the noun itself. Third, the term